Pendidikan Karakter Qur’ani Sebagai Upaya Membudayakan Nilai-Nilai Keislaman dikalangan Mahasiswa - M. Dimas Arfan Adi Subhakti; Ahmad Khoirul Mustamir; Qurrota A'yun (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Qur’anic Character Education is a process of character formation based on the moral, spiritual, and ethical values of the Qur’an. This study examines its role in cultivating Islamic values among university students. Using a qualitative descriptive approach through literature review and observation of Islamic higher education practices, the study explores how Qur’anic values are internalized within academic and social environments. The findings indicate that Qur’anic character education plays a significant role in developing students with integrity, religiosity, and noble character. Values such as honesty (ṣidq), responsibility (mas’ūliyyah), trustworthiness (amānah), and compassion (raḥmah) are fostered through learning activities, habituation, and exemplary conduct. The implementation is supported by curriculum integration, religious programs, institutional policies, and Islamic student organizations. However, challenges remain, including globalization, value secularization, and limited integration between religious and general education. Overall, Qur’anic character education functions as a strategic approach to strengthening an Islamic academic culture and preparing students who combine knowledge, morality, and social responsibility.